THE ROLE AND IMPORTANCE OF THE SRNA NEWS AGENCY IN THE MEDIA SPACE OF THE REPUBLIC OF SRPSKA - Jokić, Miroslav; Vucetic, Vuk (Politeia, 2024)
News agencies function as 'wholesalers' of news, collecting news from various parts of the world, shaping it, and distributing it to their clients, mainly traditional mass media, and/or end users, the audience. Since their beginnings in the 19th century, agencies have been essential 'gatekeepers' defining the 'agenda' of mass media and, thus, practically the entire world. Additionally, news agencies represent a pillar of national identity, similar to the national bank, the army, or the post office; they symbolise statehood. Countries that were liberated in waves of anti-colonial struggles, immediately before or shortly after gaining independence, started their own national news agencies, representing one of the symbols of their independence. The Srna is the first and only news agency in the Republic of Srpska, and one of the leading agencies in Bosnia and Herzegovina, servicing a large number of mass media with its content. Since its inception, the Srna news agency has performed its informative role, maintaining a developed network of correspondents in the country, as well as in all major centers in Europe and around the world. The Srna also keeps pace with modern technological challenges; since its inception, it has offered photo and phono services, and since 2016, it has also provided video services, making it one of the most advanced modern news agencies. It can be said that the Srna has been essentially a witness, but also a participant, in all major socio-political, cultural, and historical events in the Republic of  Srpska. However, the agency not only mediates information and news but also, in times of crisis, contributes to a kind of social homogenisation. As part of international communication highways, this agency represents an important agent of international communication. The inclusion of Srna in international communication highways, through which all major news in the world travels, has been an important part of a kind of international and political affirmation of the Republic of Srpska. Therefore, it can be said that the Srna news agency  was actually created based on two primary goals: first, to inform domestic media and the public about the most significant local and global events, and secondly, to inform the world about events in Bosnia and Herzegovina and the Republic of Srpska. Finally, the Srna was one of the main drivers of cultural life in the Republic of Srpska in the early nineties of the 20th century. As an important media company, an agent of international communication, and an important initiator of cultural life, among other things, this enterprise was the initiator of the establishment of cultural institutions (Srna film, Srna fest), a sponsor of various cultural events (Monodrama Festival of the Republic of Srpska), and it appeared as a publisher of books by domestic writers.
Keywords: News agency; Srna News agency; international communication; informative role; Republic of Srpska